Determinasi Pengungkapan Emisi Karbon di Indonesia: Kajian Profitabilitas, Kinerja Lingkungan, Tekanan Stakeholder dan Media Exposure - Salsabila, Shofiyah Nugraha; Aristantia, Selvia Eka (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Climate change and increasing carbon emissions have become urgent global challenges that require stronger corporate accountability. In Indonesia, carbon emission disclosure remains voluntary and inconsistent, raising questions about its determinants. This study aims to provide a comprehensive analysis of internal and external factors influencing carbon emission disclosure, specifically profitability, environmental performance, stakeholder pressure, and media exposure. Using a literature review approach, 20 peer-reviewed articles published between 2021 and 2025 were systematically selected and analyzed through content analysis. The findings reveal that profitability shows mixed results, ranging from positive to insignificant or even negative effects, depending on industrial context and management policy. Environmental performance tends to positively influence disclosure, especially among firms with high PROPER ratings, though some studies still report weak relationships. Stakeholder pressure generally encourages greater disclosure, yet in certain regulatory settings it may be insignificant or negative. Media exposure demonstrates inconsistent roles, with some studies finding it supportive, while others consider it reactive and limited. These variations highlight that carbon emission disclosure practices in Indonesia are not yet standardized and are shaped by industry characteristics, regulatory strength, and managerial discretion. The study contributes by synthesizing recent evidence and offering implications for regulators, corporations, and future research on environmental transparency.